A genome wide association study of pulmonary tuberculosis susceptibility in Indonesians - Png Eileen; Alisjahbana Bachti; Sahiratmadja Edhyana; Marzuki Sangkot; Nelwan Ron; Balabanova Yanina; Nikolayevskyy Vladyslav; Drobniewski Francis; Nejentsev Sergey; Adnan Iskandar; van de Vosse Esther; Hibberd Martin L; et al. (BMC, 2012)
Abstract Background There is reason to expect strong genetic influences on the risk of developing active pulmonary tuberculosis (TB) among latently infected individuals. Many of the genome wide linkage and association studies (GWAS) to date have been conducted on African populations. In order to identify additional targets in genetically dissimilar populations, and to enhance our understanding of this disease, we performed a multi-stage GWAS in a Southeast Asian cohort from Indonesia. Methods In stage 1, we used the Affymetrix 100 K SNP GeneChip marker set to genotype 259 Indonesian samples. After quality control filtering, 108 cases and 115 controls were analyzed for association of 95,207 SNPs. In stage 2, we attempted validation of 2,453 SNPs with promising associations from the first stage, in 1,189 individuals from the same Indonesian cohort, and finally in stage 3 we selected 251 SNPs from this stage to test TB association in an independent Caucasian cohort (n = 3,760) from Russia. Results Our study suggests evidence of association (P = 0.0004-0.0067) for 8 independent loci (nominal significance P < 0.05), which are located within or near the following genes involved in immune signaling: JAG1, DYNLRB2, EBF1, TMEFF2, CCL17, HAUS6, PENK and TXNDC4. Conclusions Mechanisms of immune defense suggested by some of the identified genes exhibit biological plausibility and may suggest novel pathways involved in the host containment of infection with TB.